Advanced Polymer Nanocomposites - Liu, Ting-Yu; Cheng, Yu-Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue, entitled "Advanced Polymer Nanocomposites", collects high-level original and review papers, focused on scientific discussions and practical applications in the field of functional polymer nanocomposites, including (a) optoelectronic materials (papers 1-6), (b) biomedical materials (papers 7-12), and (c) other functional polymer nanocomposites (papers 13-18).